Lumbar Epidural Abscesses: A Systematic Review. Issue 4 (December 2018) - de Leeuw, Charles N.; Fann, Patrick R.; Tanenbaum, Joseph E.; Buchholz, Avery L.; Freedman, Brett A.; Steinmetz, Michael P.; Mroz, Thomas E.
Study Design: Systematic review. Objectives: Spinal epidural abscesses (SEAs) are rare, but when missed or when diagnosis is delayed, SEA can lead to permanent neurological impairment or death. Limited information exists on the optimal treatment modalities for SEA, especially in the lumbar spine. We synthesize the current literature to identify the clinical features, diagnosis, management, and outcomes of lumbar SEA. Methods: Queries in 4 databases—EMBASE, MEDLINE, Scopus, and Web of Science—were performed using comprehensive search terms to locate published literature on lumbar SEA. Results: Ten articles reporting results for 600 cases of lumbar SEA were included, published between 2000 and 2017. Negative prognostic factors included diabetes, older age, methicillin-resistant Staphylococcus aureus, immune compromise, and more severe disease at presentation. Early first-line surgically treated patients responded better, specifically in terms of motor recovery, than those undergoing medical management or failing medical treatment, despite generally worse initial presentation. Elevated C-reactive protein, leukocytosis, and positive blood cultures predicted medical management failure. Conclusions: This systematic review provides guidance to neurological and orthopedic spine surgeons seeking the best treatment for lumbar-localized SEA. This study is limited by a dearth of high-quality publications to support evidenced-based management recommendations. Surgical treatment appears to provide better outcomes than medical treatment alone, especially in those who present with a motor deficit. Further investigation is needed to confirm this finding. What is clear is that early recognition and treatment remains crucial to minimizing morbidity and mortality of SEA.